Management of Facilities, Infrastructure and Human Resources for Optimizing Learning in Dayah - Hidayatullah, Syarif; Hibban, Ibnu; Salabi, Agus Salim (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
The importance of facilities, infrastructure and human resource management in creating a quality learning environment, especially at Dayah as a traditional Islamic educational institution which faces various limitations. This research discusses the management of facilities, infrastructure and human resources (HR) in Dayah to increase learning effectiveness. Dayah, as a traditional Islamic educational institution in Aceh, faces challenges in managing facilities and human resources which are often limited. This research aims to evaluate the condition of facilities and infrastructure, HR management, and their contribution to the quality of learning. A qualitative approach is used through case studies. Data was obtained through observation, interviews with related informants, and documentation. The research results show that the management of facilities and infrastructure is not optimal, characterized by a lack of adequate planning, maintenance and distribution of facilities. On the other hand, human resource management, including teacher placement and training, plays an important role in utilizing facilities to support learning. Inhibiting factors include limited budget, space, and attention to facility maintenance. Synergistic management between facilities, infrastructure and human resources can create a conducive learning environment, improve the quality of education, and support the achievement of Dayah's vision as a superior Islamic educational institution. An integrated strategy is needed to overcome challenges and improve the quality of education in Dayah. It is hoped that this research can become a basis for policy makers, Dayah managers and other stakeholders in formulating more effective strategies for managing facilities, infrastructure and human resources, so as to improve the quality of learning and create a more sustainable education system.